Expert Opinion on Managing Chronic HCV in Patients with Neuropsychiatric Manifestations. (January 2018) - Forton, Daniel; Weissenborn, Karin; Bondin, Mark; Cacoub, Patrice
Neurological manifestations of HCV infection appear to be under-recognized in clinical practice despite the majority of HCV-infected patients experiencing symptoms such as fatigue, depression and cognitive dysfunction. There is also growing evidence for a link between HCV infection and an increased risk of Parkinson's disease. The mechanism underpinning the association between HCV and these neuropsychiatric syndromes still requires further investigation. Here we review the pre-clinical and clinical evidence for a link between HCV and effects on the central nervous system leading to neuropsychiat-ric syndromes. Lastly, we describe how improvements in neuro psychiatric manifestations of HCV following treatment have been observed, which is subsequently refected in an overall improvement in health-related quality of life.